Using Three Steps Interview Method To Improve Students’ Writing Ability In Descriptive Text At The Tenth Grade Of Sma N I Sampaga - Susiandari, Ariawati (JIMAD : Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this research is to know how well the Three Steps Interview Method to Improve Students’ Writing Ability in Descriptive Text. This research was use an experimental design and conducted for two months in which it was consisted of eighth meetings, the first meeting was given pre-test, the second until seventh was given treatment and the last meeting was given post-test. The study was taken by at the tenth grade students of SMA N I Sampaga and here the research took class X. After doing the steps, the researcher got some data. The mean score of pre-test was 56,10 and post-test was 74,26. While the range of mean score from pre-test to post-test is 17,53. The standard deviation of pre-test is 8,95 and post-test is 10,54. The range of standard deviation from pre-test to post-test is 1,59. It could be conclude that after giving treatment to the students, the mean score in post-test (73,63) is higher than pre-test (56,10) and standard deviation in post-test (10,54) is higher than pre-test (8,95). The result of t-test was 12,02 while t- table value was 1.734. It shows that the t-test value is greater than the t-table value (12,02>1.734). It means that there was significant different between after giving treatment because t-test was greater than t-table. Based on the data, the research can be conclude that the use of Three Steps Interview Method can improve students’ writing ability in descriptive text at the tenth grade of SMA N 1 SAMPAGA.